2000
DOI: 10.1093/brain/123.2.366
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of midbrain catecholaminergic neurons in very old human subjects

Abstract: Parkinson's disease is characterized by a progressive degeneration of dopaminergic neurons in the midbrain, yet the cause of this neuronal loss is still unknown. It has been hypothesized that Parkinson's disease could be the consequence of accelerated ageing. In order to reveal a possible common process during ageing and Parkinson's disease neurodegeneration, catecholaminergic neurons of five anatomical regions of the brainstem (substantia nigra, central grey substance, ventral tegmental area, peri- and retror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
84
1
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 24 publications
10
84
1
8
Order By: Relevance
“…A previous morphological study of the TH (+) neurons in the human SN found no correlation of cell body size with age [27]. Although stereological studies of the SN have not examined the volume of TH (+) neurons in normal ageing, there is evidence for a close correspondence between pigmented and TH (+) neurons [2,7].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A previous morphological study of the TH (+) neurons in the human SN found no correlation of cell body size with age [27]. Although stereological studies of the SN have not examined the volume of TH (+) neurons in normal ageing, there is evidence for a close correspondence between pigmented and TH (+) neurons [2,7].…”
Section: Discussionmentioning
confidence: 85%
“…Kubis et al [27] did not find a significant loss of TH (+) in the SN, nor in other midbrain regions, in a series of 21 control subjects who died at ages 44-110. In contrast, we have shown a 36% (P < 0.001) loss of TH (+) SN neurons in older controls compared to younger subjects.…”
Section: Discussionmentioning
confidence: 88%
“…Hence oxidative stress produced during PD is likely the consequence of H 2 O 2 production due to a combination of dopamine oxidation, GSH depletion and Fe 2+ generated from neuromelanin, thus allowing Fenton reaction to proceed at a considerable rate leading to neuronal death. This hypothesis gains support from the observation that neuromelanincontaining neurons are preferentially lost during the course of PD (31). It remains to be elucidated whether iron accumulation precedes injury of pigmented neurons or occurs as a consequence of neuronal degeneration.…”
Section: +mentioning
confidence: 84%
“…Perfusion deficits have also been observed before the onset of clinical symptoms in other neurodegenerative disorders, which suggests that the deficits contribute to the pathogenesis of the disease (Storkebaum and Carmeliet, 2004). Conflicting results have been obtained in different studies, with either an age-dependent depletion or no change in DA neuron counts, which may be attributable to a number of methodological variables (Kubis et al, 2000;Collier et al, 2007). However, the present results support observations of a progressive functional decline in the SNc and increased vulnerability to injury with age.…”
Section: Discussionmentioning
confidence: 99%